Controlling impurity effects in phosphogypsum calcination: a combined regression and DFT study for optimizing β-hemihydrate gypsum production - Manman Lu; Wei Ma; Ze Guo; Yunpeng Shi; Mingxia Liu; Hanquan Zhang (Materials Research Express, 2025)
The preparation of β -hemihydrate gypsum by calcining is an effective way to consume phosphogypsum (PG) on a large scale at low cost. However, the impurities in the PG will affect the dehydration process of dihydrate gypsum, leading to a reduced content of β -hemihydrate gypsum in the final product. Unfortunately, the extent and mechanisms by which these impurities influence the dehydration process remain unclear. This study investigates the effects of four typical impurities SiO _2 , NaF, Ca _3 (PO _4 ) _2 , graphite on gypsum phase distribution through calcination experiments. Furthermore, the degree of impact and underlying mechanisms of these impurities on the dehydration process were further analyzed using regression analysis and density functional theory (DFT) calculations. The results indicate that when the concentrations of Ca _3 (PO _4 ) _2 , NaF, SiO _2 , and graphite are below 0.6%, 0.3%, 1.0%, and 0.1%, respectively, their influence on the β -hemihydrate gypsum content is minimal. The regression analysis revealed that the effect degree of the four impurities on the β -hemihydrate gypsum content in product is in the order of SiO _2 > NaF > Ca _3 (PO _4 ) _2 > Graphite. The primary mechanism is related to differences in the adsorption energies of water molecules on the lattice planes of the impurities. Water molecules are more readily adsorbed onto SiO _2 surfaces, where they subsequently react with β -hemihydrate gypsum during the later stages of dehydration, causing rehydration to dihydrate gypsum.